Market Liberalization and Development: South Korean and Philippine Telecommunications Service Industry in the 1990s - Kim, Dong-Yeob (Kasarinlan: Philippine Journal of Third World Studies; Vol 17 No 2 (2002): Information Technology, 2008)
This study examines the South Korean and Philippine telecoms service market liberalization in the 1990s. It does not simply compare the two countries' market liberalization cases with its trajectories and outcomes, but also sheds light on the implications of market liberalization towards the international and domestic socioeconomic order. It likewise draws attention to the question whether the global mega-trend of market liberalization addresses both material prosperity and social equality regardless of the country where one lives. The research contends that if the study of the telecoms market liberalization chiefly focuses on the economic efficiency based on market figures, it might produce a biased perception of the related issues. In order to strengthen the field of telecoms study, future research should give same weight to context-based political economy studies, which could see economic development from a normative perspective in terms of social justice and equality, both domestically and internationally.
Keywords: telecommunications, telecoms, industry, market, liberalization